Enabling digital Servitization in Philippine manufacturing: A business model innovation framework for MSMEs in the industry 4.0 ERA - Pacubas, Christina Y.; Secretaria, Norberto M.; Jr., Leoncio T. Lucero; Umpar, Najera R.; Armas, Kenneth L. (Edelweiss Applied Science and Technology, 2025)
This study explores the integration of digital servitization in Philippine manufacturing micro, small, and medium enterprises (MSMEs) amid the Industry 4.0 era. Combining the principles of servitization and digital transformation, the research aims to develop a Business Model Innovation (BMI) framework that enables MSMEs to shift from product-centric to service-oriented strategies supported by digital technologies. Employing a mixed-methods, exploratory sequential design, the study conducted policy analysis, surveys across three key regions, and qualitative case studies. Findings reveal that while many MSMEs remain reliant on manual operations, some are beginning to adopt basic digital tools and limited service innovations. Barriers to digital servitization include limited digital literacy, financial constraints, and infrastructural deficiencies, while key enablers include entrepreneurial motivation and pandemic-induced necessity. A four-phase BMI framework is proposed to guide MSMEs through assessment, strategic alignment, deployment, and continuous improvement in adopting digital servitization. This framework offers actionable insights for policymakers, industry leaders, and entrepreneurs aiming to enhance MSME competitiveness, resilience, and value creation in the context of a rapidly evolving digital economy.